1999
DOI: 10.1104/pp.121.3.905
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Profiles of Surface pH and Elongation Growth in Maize Roots

Abstract: High-resolution profiles of surface pH and growth along vertically growing maize (Zea mays) primary root tips were determined simultaneously by pH-sensitive microelectrodes and marking experiments. Methodological tests were carried out that proved the reliability of our kinematic growth analysis, while questioning the validity of an alternative technique employed previously. A distal acidic zone around the meristematic region and a proximal one around the elongation zone proper were detected. This pattern as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
63
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 39 publications
11
63
0
Order By: Relevance
“…Means 6 SE, n 5 6. of surface proton flux determined by us with pH profiles determined by carefully moving microelectrodes along the surface of the maize root elongation zone (Peters and Felle, 1999) reveals close similarities. In both cases, acidification peaked at around 4 mm from the root apex and then declined; in both cases, there appeared to be a small subsidiary peak of enhanced acidification centered at around 1 mm from the apex.…”
Section: Root Segmental Elongation and Acidification Show Qualitativementioning
confidence: 88%
See 4 more Smart Citations
“…Means 6 SE, n 5 6. of surface proton flux determined by us with pH profiles determined by carefully moving microelectrodes along the surface of the maize root elongation zone (Peters and Felle, 1999) reveals close similarities. In both cases, acidification peaked at around 4 mm from the root apex and then declined; in both cases, there appeared to be a small subsidiary peak of enhanced acidification centered at around 1 mm from the apex.…”
Section: Root Segmental Elongation and Acidification Show Qualitativementioning
confidence: 88%
“…Moreover, additions of 1 mM KCN, in order to inhibit oxidative phosphorylation, inhibited wall acidification measured in this way within 15 min, even though it would not be expected to affect the pH of mucilage at the root surface (data not shown). Similarly, Peters and Felle (1999) showed that cyanide rapidly dissipated acidification measured along the surface of the maize root elongation zone with pH-sensitive microelectrodes and also inhibited growth. Such findings suggest that wall acidification is an actively ongoing process.…”
Section: Root Segmental Elongation and Acidification Show Qualitativementioning
confidence: 99%
See 3 more Smart Citations